Determining Root Cause of Construction Waste Generation: A Global Context - Suaathi Kaliannan; Sasitharan Nagapan; Abd Halid Abdullah; Samiullah Sohu; Ashfaque Ahmed Jhatial (Civil Engineering Journal, 2018)
Construction sector is one of the main sectors in contributing Gross Domestic Product (GDP) growth rate in every developing country. The rapid growth of this sector directly produces a huge amount of construction waste. Hence, to find out the main root causes of the generation, this paper aimed to determine root causes of the construction waste generation in the construction sector. The research is carried out through triangulation technique (questionnaire survey and practitioner’s validation). This technique is adopted to facilitate cross validation by analysing 38 articles and then the final results have been validated by construction practitioners. A total of 80 root causes were identified from 38 articles and the 5 main root causes determined have scored more than 50% out of the total number of articles. Finally, the result was validated and found out that 87.5% of construction practitioners agree with the findings. The agreed root causes are ‘Constant design changes’, ‘Incorrect storage of materials’, ‘Poor handling of materials’, ‘Effect of weather’ and ‘Mistakes while ordering from suppliers’. Therefore, these initial findings will be able to aid the construction practitioner (contractors, consultants and developers) to be aware of the root causes that is mostly causing construction waste generation.